Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan Bukalapak - Ego Muhammad, Samudera Witjaksono; Hamdani, Endah Nuraini (Research Center and Case Clearing House PPM School of Management, 2021)
Human resources have a very important role in the running of a company. Every employee is required to work as well as possible because employee performance determines the success of the company to achieve its goals. In order for employees to produce good performance, companies need to pay attention to the factors that affect employee performance, namely the work environment. The work environment is divided into 2 (two) namely the physical work environment and the non-physical work environment. This study aims to determine the effect of physical and non-physical work environments on Bukalapak employees' performance. This study uses quantitative research methods through multiple linear regression which includes the t test and F test. Data were collected using a questionnaire with a Likert scale measurement. Digital questionnaires using Google Form were distributed to all 140 employees with a return rate of 100 questionnaires. Furthermore, data processing is carried out using regression analysis. The test results show that the physical work environment, non-physical work environment and both simultaneously have a significant effect on employee performance.